Recanalization Rates and Complications of Post-Endovenous Microwave Ablation in Chronic Vein Insufficiency with Large GSV Diameter - Herwirastri, Novinda; Muradi, Akhmadu (Jurnal Locus Penelitian dan Pengabdian, 2025)
Endovenous Microwave Ablation (EMA) is one of the thermal ablation modalities to treat chronic venous insufficiency (CVI). The effectiveness and safety of EMAs in large-diameter saphena magna veins (GSVs) still require further research. This study aimed to compare the rates of recanalization and post-EMA complications in CVI patients with GSV diameters of <8 mm and ?8 mm. This retrospective cohort study used data from 54 patients from a multicenter (January 2023 – May 2025). Statistical analysis was performed with an unpaired t-test and a Chi-square test. The rate of venous occlusion reached 100% in both groups. The recanalization rate at 3 months post-procedure was higher in the GSV group ?8 mm (11.1%) compared to the GSV <8 mm (3.7%), although the difference was not statistically significant (p=0.299). There were no significant differences in complications of ecchymosis, thermal skin injury, and paresthesia. However, pain was reported to be significantly higher in the ?8 mm GSV group (33.3% vs 7.4%; p=0.018). The EMA is effective in achieving occlusion in a wide range of GSV diameters, but patients with a GSV of ?8 mm (especially ?10 mm) have a higher tendency to recanalize and post-procedure pain. Additional strategies are needed to be considered to increase effectiveness and comfort in the group.